Natural convection in porous media-filled triangular enclosure with a conducting thin fin on the hot vertical wall - Varol, Y.; Öztop, Hakan Fehmi; Pop, I. (Professional Engineering Publishing Ltd, 2008)
The flow and heat transfer in a triangular enclosure filled with a fluid-saturated porous medium with a conducting thin fin on the hot vertical wall has been numerically analysed. The Darcy law model was used to write the governing equations and they were solved using a finite-difference method. Computations were carried out to analyse the effects of the Rayleigh number, length and location of fin, and thermal conductivity ratio. Results were presented for the local and mean Nusselt numbers, streamlines, and isotherms. It was found that attaching the conductive thin fin affects the heat transfer, flow fields, and temperature distributions. It was also found that heat transfer was reduced when the thin fin was attached onto the wall.
Keywords: thin fin; porous media; conjugates heat transfer; triangular enclosure